2007
DOI: 10.1590/s1806-83242007000200008
|View full text |Cite
|
Sign up to set email alerts
|

Forces in stainless steel, TiMolium® and TMA® intrusion arches, with different bending magnitudes

Abstract: , Vbend intrusion arches with different magnitudes of flexion. The sample consisted of rectangular-section wires, caliber .017" x .025", with ten arches of each alloy. All V-bends were made 48 mm from the midline, using the same phantom upper jaw, maintaining the same distance between the tubes fixed to the molars and the midline. Loads necessary to deflect the arches by 5, 10, 15 and 20 mm were measured by means of an Instron dynamometer with a 1 kgf load cell. Calculations for sample size confirmed the suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The result of the present study showed that stainless steel arch wire material provide the lowest friction resistance in wet condition followed by titanium molybdenum alloy (β-titanium TMA), then Nitinol (NiTi), and copper nickel titanium (Cu Ni Ti) which reported the highest friction resistance. Many studies (14,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) reported the superiority of stainless steel archwires as it was associated with the least amount of friction but followed by Ni Ti while beta titanium exhibited the highest frictional resistance. This was explained by the increased surface roughness of β-titanium wire as compared with stainless steel arch wire as reported by scanning electron microscope and laser spectroscopic picture (26,43) .…”
Section: Discussionmentioning
confidence: 99%
“…The result of the present study showed that stainless steel arch wire material provide the lowest friction resistance in wet condition followed by titanium molybdenum alloy (β-titanium TMA), then Nitinol (NiTi), and copper nickel titanium (Cu Ni Ti) which reported the highest friction resistance. Many studies (14,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) reported the superiority of stainless steel archwires as it was associated with the least amount of friction but followed by Ni Ti while beta titanium exhibited the highest frictional resistance. This was explained by the increased surface roughness of β-titanium wire as compared with stainless steel arch wire as reported by scanning electron microscope and laser spectroscopic picture (26,43) .…”
Section: Discussionmentioning
confidence: 99%
“…Before extraction, premolars in experimental groups were submitted to 24 hours of moderate or severe orthodontic force application. Both experimental groups used a cantilever made of 0.017 Â 0.025 TMA wire, which is ideal for the experiment because of its rectangular shape and its long transverse diameter that allows proper buccolingual control with an adequate elasticity module (17)(18)(19)(20). The activation angle controls the direction of the force exerted by a cantilever.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the systems using TMA wire had a higher friction coefficient regardless of the type of bracket used. In addition, TMA has been shown to present lower modulus of elasticity, springback greater than that of steel 8 . With regard to the brackets, the slots of metallic brackets exhibited less roughness compared to those of polycarbonate and ceramic ones.…”
Section: Discussionmentioning
confidence: 99%